Pemanfaatan Tulang Ikan Patin (Pangasius sp.) sebagai Adsorben untuk Penjernihan Air Gambut - Yayan Satria; Ermal, Dini Aulia Sari; Lisa Legawati; Cici Maarasyid; Israyandi, Israyandi; Dwi Annisa Fithry; Viona Aulia Rahmi; Delvina Sari (Fakultas Teknik UMRI, 2024)
Peat water is raw water which is used as a source of clean water by the people of Pekanbaru. However, after testing according to the Regulation of the Minister of Health of the Republic of Indonesia for clean water standards No. 416/MENKES/PER/IX/1990 the results of measuring the color and turbidity value of peat water are above the quality standards, namely 219 TCU and 15.1 NTU. This value is very far from the color and turbidity quality standards with respective concentrations of 15 TCU and 5 NTU. Therefore, in this research, an adsorption process was carried out using an adsorbent from Patin bone waste (Pangasius sp.) typical of Riau province by utilizing a physical activation process to open pores and help facilitate absorption. The variable used in this research were adsorbent mass and stirring speed. For adsorbent mass there was a variation of 0.1; 0.3; 0.5; and 0.7 grams while the stirring speed was 50, 100, and 150 rpm with a stirring time of 120 minutes and each sample had a particle size of 100 mesh. The results of this adsorption process obtain the best efficiency value at Patin bone mass of 0.7 grams with a stirring speed of 100 rpm. The color reduction efficiency reached 96.35%, namely 8 TCU, while the turbidity reduction efficiency at Patin bone mass of 0.7 grams with a stirring speed of 100 rpm reached 92.72%, namely 1.1 NTU.